Status prawny komisji rewizyjnej jako element ładu korporacyjnego gminy - Szczepaniak, Rafał (Wydawnictwo Naukowe UAM, 2015)
The author examines one of the aspects of the so-called corporate governance of the municipality, which is the legal status of its audit committee. According to the author the importance of this issue stems from the fact that the audit committee is an instance of internal institutional audit in the municipality, but also of the local community’s supervision over the activities of the municipal executive authority. As is known, since 2002 the municipal executive powers are exercised individually by the wójt (elected municipal governor) in rural communities, and by the mayor or president in towns and cities. The author argues that, despite 25 years of the Local Government Act being in force, the legal status of the audit committee as provided by the Act is not fully accurate and consistent. He proves the veracity of his claims by presenting examples of court judgments and decisions of state regulators over the local government units. What can be concluded from the said judgments and decisions is that the in current legal environment it depends on the will of the wójt, mayor, or president whether the audit committee will be able to carry out its auditing activities in a fully eff ective way. Such a condition in which the eff ectiveness of the audit depends to a large extent on the will of the audited entity, must be evaluated negatively. According to the author, in practice, one of the legal obstacles in conducting effective supervision by the audit committee is also the not entirely precise regulation of the access by members of audit committees to the information on the functioning of the local government units. Therefore, the author puts forward a proposal de lege ferenda of introducing to Polish law a special provision guaranteeing the members of the audit committee full access to the information about the functioning of the local government entities, with the exception of the information covered by the state and offi cial secrecy clause.
The legal status of the audit committee, as part of corporate governance of the municipality
Keywords: corporate governance of the municipality; audit committee in the municipality; access to the information; auditing activity